(3GdebGUOs - (3ejKe GdHMQGfj , ceGd GdOjf,J (B681 (3g` s ((3eMeO Hf WGgQ GdSeGhi s)
(3ChdgG (B:s
(3hHYO adeG cGf TQa GdYdhe HTQa GdeYdhe acdeG cGf GdeYdhe CLd hCYdi cGf GdYde Hg HGdQYGjg Chdi s
(3BNQgG (B:s
(3hEPG LGR ai GdWQajf ade dGjLhR eKdg ai GdhGSWI CYfi WHbI GdChdjGAJe cJGH GdebGUO GdeTghQ HGdbhGYO s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B336 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B55s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds